EKSPLORASI DAN INTERNALISASI KESADARAN PENTINGNYA HOSPITALITY DALAM PARIWISATA BANDAR LAMPUNG - Sanjaya, Fitri Juliana; Fahmi Tarumanegara; hasbi sidik; Luerdi; Michael Rizky (Ragom Jurnal Pengabdian Masyarakat, 2025)
Bandar Lampung is one of the destinations in Sumatera that is developing tourism potential and hosting events to increase visitor numbers. Tourist visits from neighborhood areas have demonstrated that both the city of Bandar Lampung and the province of Lampung are not priorities among destinations. Such low achievement indicates another factor besides infrastructure and destination eligibility that is needed by tourists or visitors. The community service team assumed the contributing factors, such as value internalization and hospitality practices far from compliant with the market target. This community service program aimed to explore and internalize awareness of the importance of hospitality in tourism in Bandar Lampung. Three different groups of youth participants were involved. The program can leverage the participants’ understanding of hospitality practices. In addition, the commitment to creating the ‘Lampung Punn’ community has been conceived to promote hospitality values more widely.